Serum Level of Soluble CD163 May Be a Predictive Marker of the Effectiveness of Nivolumab in Patients With Advanced Cutaneous Melanoma - Fujimura, Taku; Sato, Yota; Tanita, Kayo; Kambayashi, Yumi; Otsuka, Atsushi; Fujisawa, Yasuhiro; Yoshino, Koji; Matsushita, Shigeto; Funakoshi, Takeru; Hata, Hiroo; Yamamoto, Yuki; Uchi, Hiroshi; et al. (Frontiers in Oncology, 2018)
Antibodies against programmed cell death protein 1, such as nivolumab and pembrolizumab, are widely used for treating various cancers, including advanced melanoma. Nivolumab significantly prolongs survival in patients with metastatic melanoma, and sequential administration with lipilimumab may improve outcomes when switched at the appropriate time. Biomarkers are therefore needed to evaluate nivolumab efficacy soon after first administration. This study analyzed serum levels of soluble cluster of differentiation 163 (sCD163) in 59 cases of advanced cutaneous melanoma and 16 cases of advanced mucosal melanoma treated using nivolumab. Serum levels of sCD163 were significantly increased after 6 weeks in responders compared to non-responders after initial administration of nivolumab for cutaneous melanoma. In contrast, no significant difference between responders and non-responders was seen among patients with non-cutaneous melanoma. These results suggest that sCD163 may be useful as a biomarker for selecting patients with advanced cutaneous melanoma most likely to benefit from anti-melanoma immunotherapy.